2018
DOI: 10.1111/rda.13255
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of vaginal discharge characteristics evaluated by Metricheck device to metabolic status in postpartum dairy cows

Abstract: The relationship between vaginal discharge characteristics and metabolic status has been studied in postpartum dairy cows. Vaginal discharges at 2-6 weeks postpartum were scored weekly on a 1 (clear) to 5 (purulent material with stench) scale using the Metricheck device and classified into three groups as follows: Endometritis group (n = 19), greater than or equal to score 4 until 3 weeks postpartum; Delayed involution group (n = 9), score 2 or 3 after having score 1; Healthy group (n = 23), cows except those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Both groups showed smooth recovery compared to previous studies (Kawashima et al, 2018;Stephen et al, 2019). The PMN percentages at 3 and 5 weeks were consistent with those of previous reports (Gilbert & Santos, 2016;Stephen et al, 2019) and were comparable between the RPL and CON groups.…”
Section: Itemsupporting
confidence: 91%
“…Both groups showed smooth recovery compared to previous studies (Kawashima et al, 2018;Stephen et al, 2019). The PMN percentages at 3 and 5 weeks were consistent with those of previous reports (Gilbert & Santos, 2016;Stephen et al, 2019) and were comparable between the RPL and CON groups.…”
Section: Itemsupporting
confidence: 91%
“…Others have reported that endometrial epithelial cells exhibited reduced PGF 2α production when treated with exosomes isolated from plasma of cows with a uterine infection compared with those treated with exosomes isolated from healthy cows (Almughlliq et al, 2017). Additionally, concentrations of PGFM tended to be lower in cows with endometritis (based on Metricheck reading) than healthy cows (Kawashima et al, 2018). Differences between these studies could be due to differences in cow breeds, methods of classifica-tion of endometritis or uterine infection, and in vitro versus in vivo analysis.…”
Section: Discussionmentioning
confidence: 97%
“…PGF 2α is necessary for the process of spontaneous uterine involution [19][20][21]. Kawashima et al [11] reported that the blood concentration of the PGF 2α metabolite 13,14-dihydro-15-keto-PGF 2α (PGFM) tended to be higher in cows with delayed spontaneous uterine involution and lower in cows with endometritis than in healthy cows during W3. The cows with normal uterine involution showed a negative correlation between the blood PGFM level and the time to complete uterine involution.…”
Section: Discussionmentioning
confidence: 99%
“…The VDS was determined at W2, W3, and W5 using a Metricheck device (Simcro Tech Ltd., Hamilton, New Zealand) that comprised a stainless-steel rod and a silicon cup. The VDS assessment method was similar to the method described by [11] with slight modifications as follows: VDS1 = clear or translucent mucus; VDS2 = mucus containing flecks of white pus or off-white purulent material; VDS3 = discharge containing <50% purulent material; and VDS4 = discharge containing >50% purulent material.…”
Section: Experiments 1: Comparison Of the Effects Of Intrauterine Infusion Of A Chitosan Solution Versus Intramuscular Administration Of mentioning
confidence: 99%